Conversion from the frequency of chromosome translocations in T-lymphocytes to the bone marrow dose in the long-term period after internal 89,90 Sr exposure - E. I. Tolstykh (Радиационная гигиена)
Cytogenetic Fluorescence In Situ Hybridization studies, that allow assessing the frequency of stable chromosome  aberrations  in  circulating  T  lymphocytes,  are  commonly  used  in  retrospective  dosimetry  in  cases of uniform whole-body exposure. In the event of 89,90Sr exposure, interpretation of cytogenetic data is challenging,  especially  if  blood  sampling  occurs  long  after  the  start  of  exposure.  The  weighted  average  dose  to T-lymphocytes at the time of donor blood sampling in the long-term period after exposure to 89,90Sr does not coincide  with  the  red  bone  marrow  dose.  Previously,  we  developed  a  model  that  allows  us  to  estimate  the weighted average doses to T-lymphocytes upon 89,90Sr ingress into the body of people belonging to various age groups. In this study, the modeling results were used to estimate the conversion factors from the frequency of translocations to the red bone marrow dose, which is important for assessing radiobiological effects associated with hematological diseases. The objective of our study is to estimate numerically the conversion factors (Brbm) from the dose to lymphocytes to the dose to red bone marrow for various scenarios of 89,90Sr ingestion depending on age, sex, and time after the start of exposure. The following scenarios are considered: single, uniform chronic for six months, uniform chronic for 1-5 years, non-uniform intake for 5 years (simulates the dynamics of intake in the Techa riverside settlements in 1950-1954). As a result, it has been found that the Brbm values significantly depend on the age at the time of 89,90Sr intake. The older the person is at the start of exposure, the more the cytogenetic dose differs (it is significantly lower) from the dose to the red bone marrow. We can say that the cytogenetic dose corresponds to the red bone marrow dose only in newborns and infants. This is due to the age-related dynamics of T-cell populations. Sex does not have a significant effect on Brbm. The effect of the 89,90Sr intake duration on Brbm is the most pronounced for 15-year-old adolescents. For them, the difference in Brbm values for a single and chronic 5-year ingress reaches 13%. Non-uniform intake of 90Sr over several years does not have a significant effect on Brbm and can be modelled by a uniform intake of the same duration.